Pelatihan Pembuatan Media Pembelajaran Interaktif Berbasis Web (MPI-BeWe) Bagi Guru-Guru SD Sekecamatan Pulau Beringin, Muara Dua, Sumatera Selatan - Fathurohman, Apit; Yusup, Muhammad; Seira, Erazando Alfa; Kistiono; Pasaribu, Abidin; Samsuryadi (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2023)
The main objective of this research is to train and provide assistance to elementary school teachers in Pulau Beringin District, Ogan Komering Ulu Selatan District (OKUS) in making web-based interactive learning media (MPI BeWe). Using the Technical Assistance method in the form of Training and Workshops which is carried out by providing training and workshops with steps: socialization, practice, mentoring, and evaluation. One of the obstacles to the development of multimedia learning media is the lack of mastery of ICT-based multimedia learning media development technology by teachers so the development of ICT-based multimedia learning materials is not optimal. Especially elementary school teachers in the Beringin Island District, South Ogan Komering Ulu Regency (OKUS). After carrying out this activity, it can be concluded that elementary school teachers in Pulau Beringin District, Ogan Komering Ulu Selatan (OKUS) Regency who were participants in the training and mentoring for the creation of BeWe MPI-based learning media (Web-Based Learning Media) succeeded in making learning media in the form of blogs. The implementation of the training has been able to achieve the expected goals, this can be seen from the tasks given to participants which can be completed properly.